(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the effectiveness of Fu’s subcutaneous needling combined with acupressure massage therapy in treatment of low back pain. Subjects and methods: A clinical trial study, comparing before and after treatment, with a control group. 60 patients were divided into 2 groups: the research group treated with Fu’s subcutaneous needling combined with acupressure massage and the control group treated with Electro-acupuncture combined with acupressure massage. Results: Pain relief effect: average pain score according to the VAS scale decreased from 54,93 ± 0,74 points to 0,67 ± 0,71 points, statistically significant with p < 0.05 and better than the control group (p < 0.05). The degree of lumbar spine flexion measured by the Schober test improved significantly. In the study group, 63.3% of participants were classified as having mild limitation while 30% achieved a normal range of motion. The Schober score increased showing a statistically significant difference (p < 0.05) and a greater improvement compared with the control group (p < 0.05). Lumbar flexibility assessed by the fingertip-to-floor test also improved significantly (p < 0.05). Improvements in lumbar flexion, extension, and lateral bending were statistically significant (p < 0.05). Functional outcomes in daily activities, evaluated using the ODI, showed a more favorable trend in the study group compared to the control group, with the difference being statistically significant (p < 0.05). The mean ODI score decreased a statistically significant reduction (p < 0.01), and was comparable to that of the control group (p > 0.05). Conclusion: The combined therapy of Fu needle acupuncture and acupressure massage proved to be effective in treating low back pain associated with cold-dampness and blood stasis syndromes. The treatment demonstrated superior outcomes compared with the control group in terms of pain reduction, increased lumbar spine flexibility, improved flexion, extension, and lateral bending of the lumbar region, as well as enhanced daily functional capacity.